Negative equity in the Irish housing market: Estimates using loan level data - David Duffy; Niall O'Hanlon (The Economic and Social Research Institute (ESRI), 2013)
The sharp decline in house prices since 2007 has led to the emergence of widespread negative equity in Ireland. For a large sample of borrowers in negative equity the paper provides details on the characteristics of the borrowers and their mortgages by analysing loans taken out to purchase a primary residence in the period 2005 to 2012. The emergence of negative equity is not just about price drops. Loan characteristics such as the loan-to-value ratio and the length of the mortgage term also have a role to play. The analysis finds the situation in Ireland to be much more severe than that being experienced in other housing market downturns at present, with 64 per cent of borrowers from the period 2005-2012 in negative equity. Analysis by age gives rise to concern, with the majority of those in negative equity aged under 40 years. Traditionally, this is the age group most active in the housing market. The paper also points to the large wealth loss, in the order of exteuro43 billion, experienced by Irish households as a result of the fall in prices. With only moderate house price growth expected in the years ahead there is a generation of mortgage borrowers whose housing market experience will have been overwhelmingly negative and who will remain in negative equity for some time.
Keywords: 330